2008
DOI: 10.1016/j.ijid.2008.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus markers among blood donors in a tertiary hospital in Tabuk, northwestern Saudi Arabia

Abstract: The prevalence of HBV infection among male Saudi blood donors in the northwest region of Saudi Arabia is high compared to that reported from the central capital area (Riyadh). Public health education programs on HBV infection, adult hepatitis B immunization programs, and raising socioeconomic standards should be initiated in order to target the high-risk groups found in this study. Furthermore, a community-based study is recommended to investigate HBV infection in the northwest region of Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
47
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 15 publications
9
47
4
Order By: Relevance
“…This study detected lower HBsAg prevalence (0.8%) and lower prevalence of HBV infections (8.0%) among blood donors than had been previously reported in the southern region of the KSA [13,23], although one recent study in the Aseer province reported an HBsAg prevalence of as low as 1.03% [24]. Additionally, the cohort of donors between 16 and 21 years of age, whose birth corresponds with the HBV vaccine inclusion to EPI, showed no HBsAg and a low prevalence of HBV infections.…”
Section: Discussionsupporting
confidence: 50%
“…This study detected lower HBsAg prevalence (0.8%) and lower prevalence of HBV infections (8.0%) among blood donors than had been previously reported in the southern region of the KSA [13,23], although one recent study in the Aseer province reported an HBsAg prevalence of as low as 1.03% [24]. Additionally, the cohort of donors between 16 and 21 years of age, whose birth corresponds with the HBV vaccine inclusion to EPI, showed no HBsAg and a low prevalence of HBV infections.…”
Section: Discussionsupporting
confidence: 50%
“…In that study, a family history suggestive of HBV infection, lack of HBV vaccination and low education levels were significantly associated with the development of HBV infection. [17] We suggest that future research should focus on clarifying HBV risk behaviors and transmission in this region, including modes of transmission within families and households.…”
Section: Discussionmentioning
confidence: 99%
“…CHB is a leading cause of end-stage liver disease and hepatocellular carcinoma [2,3]. Saudi Arabia is similar to other CHB-endemic countries, where CHB is usually an outcome of vertical transmission or transmission early in life from infected family members [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported data on CHB from Saudi Arabia have focused on the prevalence of the disease [5][6][7] and the effect of HBV vaccination on reducing the rate of hepatitis B surface antigen (HBsAg) seropositivity in the country [9,10], but there are no similar data available that focus on the long-term follow-up or treatment outcome. HBV-DNA was found to be the best predictor of the severity of fibrosis, long-term outcome, progression to end-stage liver disease, the risk of hepatocellular carcinoma (HCC) and the response to therapy [2,3,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%